Representation and Equality: Basic Education Democracy in Minangkabau - Warnis Warnis (Institut Agama Islam Negeri Imam Bonjol Padang, 2016)
Social life of a village in Minangkabau is built on a tradition of democracy and mutual agreement. This study aims to explain and elaborate on the values contained in the legend and tradition as the basis of democratic education in Minangkabau. Furthermore, it also describes the potential and contribution of the custom that support the understanding of democracy and democratization process that includes: Representativeness, Sakato consensus (Sakato, an institution that accommodates the aspirations of the people), decision-making, basic freedoms and individual engagement in decision-making, and the equality of voting rights in the deliberations. This study used a qualitative approach, comprehensive interviews and documentation as data collection. The data source is the prince, traditional leaders, Nagari custom, traditional Alam Minangkabau, Bundo Kanduang, religious leaders and society. Data analyzed refers to the analysis of qualitative data presented by Alwasilah (2002). The results showed that the global concept of democracy can be united with the democracy education system brought by traditional communities. That is, people's understanding of democracy education not only refers to the idea of West democracy. However, the custom values of society can be used as the basis democratic education for Minangkabau society of the present and future. The result also shows that the Minangkabau community has first implemented democracy based on traditional values long before Western democracy applied in Indonesia, especially in Minangkabau.